2020
DOI: 10.2459/jcm.0000000000001139
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of paradoxical low-flow low-gradient aortic stenosis after transcatheter aortic valve replacement

Abstract: Aims In paradoxical low-flow low-gradient severe aortic stenosis (PLFLG AS) patients, stroke volume index (SVI) is reduced despite preserved left ventricular ejection fraction (LVEF). Although reduced SVI is already known as a poor prognostic predictor, the outcomes of PLFLG AS patients after transcatheter aortic valve replacement (TAVR) have not been clearly defined. We retrospectively investigated the post-TAVR outcomes of PLFLG AS patients in comparison with normal-flow high-gradient aortic sten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 40 publications
(89 reference statements)
0
11
0
Order By: Relevance
“…Several studies have suggested that patients with atypical aortic stenosis are a higher-risk cohort of patients hampered by an increased risk of adverse cardiovascular events. 24,25 Indeed, Saito et al 25 illustrated that diastolic dysfunction was highly prevalent in patients with severe aortic stenosis undergoing TAVR. They found that patients with increasing grades of diastolic dysfunction had higher rates of all-cause mortality at 1 year, mainly because of higher rates of cardiovascular death.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested that patients with atypical aortic stenosis are a higher-risk cohort of patients hampered by an increased risk of adverse cardiovascular events. 24,25 Indeed, Saito et al 25 illustrated that diastolic dysfunction was highly prevalent in patients with severe aortic stenosis undergoing TAVR. They found that patients with increasing grades of diastolic dysfunction had higher rates of all-cause mortality at 1 year, mainly because of higher rates of cardiovascular death.…”
Section: Discussionmentioning
confidence: 99%
“…The indication to treat paradoxical low-flow low-gradient AS is weaker than that to high gradient AS. Indeed, patients with paradoxical low-flow low-gradient AS undergoing TAVI seem to have a worse early and mid-term prognosis as compared with those with normal-flow high-gradient AS 23 …”
Section: Aortic Stenosismentioning
confidence: 99%
“…Indeed, patients with paradoxical low-flow low-gradient AS undergoing TAVI seem to have a worse early and midterm prognosis as compared with those with normal-flow high-gradient AS. 23 The role of TAVI in the emergent setting is also debated. However, a recent single-center study reported a higher survival rate in patients with decompensated AS undergoing urgent or emergent TAVI compared with those receiving urgent or emergent balloon valvuloplasty.…”
Section: Aortic Stenosismentioning
confidence: 99%
“…Aortic valve stenosis is a common valvular disease that manifests clinically as dyspnoea, angina, and syncope, and its prevalence increases with age, affecting 3% of persons more than 65 years old. [1][2][3] Severe aortic valve stenosis and the development of left ventricular hypertrophy (LVH) are associated with significant changes in microvascular haemodynamics. [4][5][6] Patients with aortic valve stenosis have been shown to have coronary microvascular dysfunction (CMD) reflected by reduced coronary flow reserve (CFR) and a high index of microvascular resistance (IMR) despite nonobstructive coronary stenosis, 4,[6][7][8][9] which limits coronary blood flow while increasing oxygen demand, causing myocardial ischaemia.…”
Section: Introductionmentioning
confidence: 99%
“…Aortic valve stenosis is a common valvular disease that manifests clinically as dyspnoea, angina, and syncope, and its prevalence increases with age, affecting 3% of persons more than 65 years old 1–3 . Severe aortic valve stenosis and the development of left ventricular hypertrophy (LVH) are associated with significant changes in microvascular haemodynamics 4–6 .…”
Section: Introductionmentioning
confidence: 99%